A Phenomenological Study of Work-Life Balance During Covid-19 Among Staff of Private Higher Educational Institutions in Malaysia: Coping with Transitions - Swa, Lee Lee (2023)
Many scholars have concluded that the formal definition of work-life balance (WLB) was ambiguous and lacked a well-developed concept when assessing the importance of creating balance. However, although the content and descriptions of the research findings varied depending on the theories used in the WLB study, these studies all focused on a similar issue: the organisations that offered a positive WLB, such as a healthy work environment to allow their employees to achieve work-related goals, have seen to increase in job performance, organisational commitment, and job satisfaction. Similar to this, the increase of "imbalance" between work and personal life, particularly as it affects people in contemporary society, might undermine job happiness and engagement. The outbreak of Covid-19 has further impacted the WLB of the staff of the Malaysian private higher educational institutions (PHEIs). The main goal of this study was to perform an in-depth analysis of the staff members' perceptions of WLB and their lived experiences as they moved in, moved through, and moved out of the Covid-19 pandemic environment. The Boundary Theory of WLB and the Schlossberg's Theory of Transition served as the theoretical foundations for the research. With its emphasis on the three transitional stages of moving in, moving through, and moving out, Schlossberg's Theory of Transition had provided a framework for an in-depth study of the staff members' experiences with the Covid-19 and how those experiences had affected their WLB during the volatility, uncertainty, complexity, and ambiguity (VUCA, such as Covid-19) environment. Twenty one (21) staff participated in the study, representing from two types of comprehensive private higher educational institutions (PHEIs; conventional and Open-Distance Learning) that offered a variety of foundation, undergraduate and postgraduate programmes, and cross-sectional (academic versus non-academic) functions of the PHEIs. Based on phenomenology approach, the Asynchronous Email Interviews (AEIs) were constructed and conducted that aimed to use one's past experiences, in this context how the participants perceived, interpreted, and gave the transition experience significance, concentrating on the components they considered were important relating to Covid-19 pandemic. The AEIs were validated, pilot tested and modified based on the recommendations of experts on WLB and Schlossberg’s Theory of Transition. The results of the actual study suggest that the degree to which the participants were able to achieve their WLB was significantly influenced by how they perceived or defined their WLB. The definitions of WLB and its attainment did not appear to differ much between the staff of conventional and ODL institutions, nor between academic and non-academic people. As far as the PHEI staff under studied were concerned, majority of them were emphatic about the well-being of their staff by providing them leave and supporting messages, if they or their family were Covid-19 positive. it was noted that none of the staff were laid-off, but some experiencing reduction in their monthly pay. These support from the immediate family, the affiliated PHEI, and the Government’s moratorium were seen effective and recommended to be continued. The analysis uncovered a number of recurring themes, including, there was no perfect WLB and its definition. The Yin-Yang Work-Life Harmony (WLH) model, and the SPARE (Sociological, Psychological, Administrative, Resources and Educational) Challenges, faced by the participants of this study especially during the trying times of the VUCA environment (in this context the Covid-19), stood out as being the two novelties of this research. It is crucial that the conclusions and follow-up suggestions made in this study find their way to policymakers at all levels, in case such VUCA calamity were iii to happen in the near future. Finally, it is advised that PHEIs provide hands-on professional development courses on developing and managing WLH for their staff. A healthy WLH is an asset to the organisation